2000
DOI: 10.1038/77000
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA heteroplasmy in cloned cattle produced by fetal and adult cell cloning

Abstract: Mammals have been cloned from adult donor cells. Here we report the first cases of mitochondrial DNA (mtDNA) heteroplasmy in adult mammalian clones generated from fetal and adult donor cells. The heteroplasmic clones included a healthy cattle equivalent of the sheep Dolly, for which a lack of heteroplasmy was reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
95
0
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 160 publications
(105 citation statements)
references
References 15 publications
8
95
0
2
Order By: Relevance
“…That is why calves derived from NT blastocysts transplanted into surrogate mothers, exhibited mtDNA heteroplasmy, induced by both cellular mosaicism of mitochondrial genome sequences and neutral (random) segregation of parental mtDNA haplotypes (the so-called mitotypes) during early embryogenesis (Steinborn et al, 1998b;Hiendleder et al, 1999;Takeda et al, 2003;Figure 3). Recently, Steinborn et al (2000) reported mitochondrial heteroplasmy in cloned cattle generated from Figure 3. Schematic diagram of intraspecies somatic cloning (nuclear transfer of allogeneic somatic cells).…”
Section: Consequences Resulting From the Transmission Of Two Mitochonmentioning
confidence: 99%
See 4 more Smart Citations
“…That is why calves derived from NT blastocysts transplanted into surrogate mothers, exhibited mtDNA heteroplasmy, induced by both cellular mosaicism of mitochondrial genome sequences and neutral (random) segregation of parental mtDNA haplotypes (the so-called mitotypes) during early embryogenesis (Steinborn et al, 1998b;Hiendleder et al, 1999;Takeda et al, 2003;Figure 3). Recently, Steinborn et al (2000) reported mitochondrial heteroplasmy in cloned cattle generated from Figure 3. Schematic diagram of intraspecies somatic cloning (nuclear transfer of allogeneic somatic cells).…”
Section: Consequences Resulting From the Transmission Of Two Mitochonmentioning
confidence: 99%
“…Thus far, the fate of foreign mtDNAs is still controversial in intraspecies cloned embryos. In the bovine nuclear transferred embryos, mitochondrial genome primarily arises from the recipient oocytes (Do et al, 2001;Meirelles et al, 2001), whereas in the others mtDNA copies appear to be heteroplasmic (Steinborn et al, 2000(Steinborn et al, , 2002Do et al, 2002;Hiendleder et al, 2003;Takeda et al, 2003) SAMIEC M.…”
Section: Consequences Resulting From the Transmission Of Two Mitochonmentioning
confidence: 99%
See 3 more Smart Citations